PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP RUMAH SAKIT MULIA AMUNTAI DI KABUPATEN HULU SUNGAI UTARA - Latte, Jumai; Sumiarni , Rina (PPPM STIA Amuntai, 2021)
The objectives of this research the effect of service quality on inpatient satisfaction at the Mulia Amuntai Hospital in Kabupaten Hulu Sungai Utara. The type of research used is explanatory. The population and sample in this study were inpatients at Mulia Amuntai Hospital from the period 9 to 30 May with a total sample of 41 respondents. Sampling technique using of purposive sampling. The data analysis technique in this study used SPSS. The results showed that service quality had a significant effect on inpatient satisfaction at Mulia Amuntai Hospital in Hulu Sungai Utara Regency, the effect was 65.10%, while 34.9% was the influence of other variables not examined in this study.